Lawrence P. Conover, ed., Revised Ordinances of the Village of Hinsdale, Illinois 1912: Printed and Published by Authority of the President and Board of Trustees of the Village of Hinsdale, Pursuant to Ordinance, Passed and Approved, February 5, 1912, Issued in Book Form, February 15, 1912 (Hinsdale, IL: Merrill Printing Company, 1912), 168-169. Chapter 26—Concealed Weapons, §§ 1-8. Undated - (:unkn) unknown (General Publisher, 1912)
Prohibtied concealed carry of any pistol, colt, slung-shot, cross knuckles, knuckles of lead, brass, or other metal,or Bowie-knife, dirk, dagger, or other dangeorus or deadly weapon. Violators shall have weapons confiscated, arrested before a warrant is issued, fined not less than five nor more than two hundred dollars.
--
Keywords: CARRY - CONCEALED